2024
DOI: 10.1029/2023sw003796
|View full text |Cite
|
Sign up to set email alerts
|

Collection, Collation, and Comparison of 3D Coronal CME Reconstructions

C. Kay,
E. Palmerio

Abstract: Predicting the impacts of coronal mass ejections (CMEs) is a major focus of current space weather forecasting efforts. Typically, CME properties are reconstructed from stereoscopic coronal images and then used to forward model a CME's interplanetary evolution. Knowing the uncertainty in the coronal reconstructions is then a critical factor in determining the uncertainty of any predictions. A growing number of catalogs of coronal CME reconstructions exist, but no extensive comparison between these catalogs has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…We have focused on characterizing and comparing properties of the interplanetary shock, sheath region, and magnetic ejecta as measured by the two spacecraft. Overall, we have found some similarities but also some profound differences between the two sets of in situ data that, although resulting from flank encounters with the structure as a whole, are characterized by a relative nonradial angular separation (∼5°) that is smaller than the typical errors associated with 3D reconstructions of CMEs based on remote-sensing data-for example, Verbeke et al (2023) found minimum uncertainties of 6°in latitude and 11°in longitude using the GCS model, and Kay & Palmerio (2024) estimated a typical difference of 4°in latitude and 8°in longitude between two independent reconstructions of the same event.…”
Section: Discussionmentioning
confidence: 74%
“…We have focused on characterizing and comparing properties of the interplanetary shock, sheath region, and magnetic ejecta as measured by the two spacecraft. Overall, we have found some similarities but also some profound differences between the two sets of in situ data that, although resulting from flank encounters with the structure as a whole, are characterized by a relative nonradial angular separation (∼5°) that is smaller than the typical errors associated with 3D reconstructions of CMEs based on remote-sensing data-for example, Verbeke et al (2023) found minimum uncertainties of 6°in latitude and 11°in longitude using the GCS model, and Kay & Palmerio (2024) estimated a typical difference of 4°in latitude and 8°in longitude between two independent reconstructions of the same event.…”
Section: Discussionmentioning
confidence: 74%
“…The DONKI values should be used for the NASA GSFC predictions and should be similar to what was used by others, but each forecaster likely has their own coronal CME reconstruction that then use to drive their model. Coronal reconstructions are notoriously uncertain (e.g., Kay & Palmerio, 2024;Verbeke et al, 2023) so we expect there could be significant variation between the inputs used by different models. We have no means of comparing with the specific values used for each prediction, but suspect we may find more significant correlations if we could.…”
Section: Variation With Cme Propertiesmentioning
confidence: 99%
“…The model inputs include both the reconstructed CME properties and the background solar wind through which the CME propagates. We know that CME reconstructions can be affected by large uncertainties (e.g., Kay & Palmerio, 2024;Verbeke et al, 2023) and that these can translate into AT errors of the order of 10 hr (e.g., Kay et al, 2020). This alone is sufficient to mask the effects of any background SW effects or inadequacies in the models.…”
Section: 1029/2024sw003951mentioning
confidence: 99%